2016
DOI: 10.1097/md.0000000000004337
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic status in relation to Parkinson's disease risk and mortality

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
30
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 29 publications
7
30
2
Order By: Relevance
“…The AMORIS Study was also cross‐linked to the Swedish Censuses in 1970, 1980, 1985, and 1990 to obtain information regarding country of birth (Sweden, other Nordic countries, other, or unknown) and socioeconomic status (low, high, or unclassified or missing) at the time of recruitment. We adjusted for socioeconomic status because it has been associated with the level of inflammatory markers and potentially also PD and ALS . Socioeconomic status was originally classified as unskilled worker, skilled worker, lower employee, intermediate employee, higher employee, self‐employed, and farmer in the AMORIS Study, and we classified unskilled worker, skilled worker, and lower employee as low socioeconomic status, and intermediate employee, higher employee, self‐employed, and farmer as high socio‐economic status.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The AMORIS Study was also cross‐linked to the Swedish Censuses in 1970, 1980, 1985, and 1990 to obtain information regarding country of birth (Sweden, other Nordic countries, other, or unknown) and socioeconomic status (low, high, or unclassified or missing) at the time of recruitment. We adjusted for socioeconomic status because it has been associated with the level of inflammatory markers and potentially also PD and ALS . Socioeconomic status was originally classified as unskilled worker, skilled worker, lower employee, intermediate employee, higher employee, self‐employed, and farmer in the AMORIS Study, and we classified unskilled worker, skilled worker, and lower employee as low socioeconomic status, and intermediate employee, higher employee, self‐employed, and farmer as high socio‐economic status.…”
Section: Methodsmentioning
confidence: 99%
“…We adjusted for socioeconomic status because it has been associated with the level of inflammatory markers 14 and potentially also PD and ALS. 15,16 Socioeconomic status was originally classified as unskilled worker, skilled worker, lower employee, intermediate employee, higher employee, self-employed, and farmer in the AMORIS Study, and we classified unskilled worker, skilled worker, and lower employee as low socioeconomic status, and intermediate employee, higher employee, self-employed, and farmer as high socio-economic status.…”
Section: Prospective Cohort Analysismentioning
confidence: 99%
“…They may be more suited to jobs with higher socioeconomic status, both at interview and in the daily routine. This would explain the new observations . Furthermore, PD‐linked mutations have been around since prehistoric times and may therefore have had a selective advantage for young people encountering situations demanding rapid responses, for example, escape or hunting activities.…”
mentioning
confidence: 79%
“…Such jobs may be demanding of deeper thought, good discrimination, and quick judgments. In a second study of >4.5 million people from the Swedish census, those with lower socioeconomic status had a lower PD incidence …”
mentioning
confidence: 95%
“…Similarly poverty is a well-cited risk factor for chronic disease and premature mortality both in Brazil and across the globe [20,21]. When specifically comparing socioeconomic status and PD mortality, Yang et al found that low-income was associated to higher mortality rates while Beard et al identified higher rates in the high-income population [22,23]. In our study, the mortality risk associated with occupational pesticide exposure was still observed when accounting for current wealth (as measured by private health insurance coverage), a history of low income, and low educational attainment.…”
Section: Discussionmentioning
confidence: 99%